That uh-oh feeling : a story about touch - Cole, Kathryn (I'm a great little kid series., 2016)
"No matter how hard she tries, Claire can't kick the soccer ball in a straight line. Her coach steps in and places his hand on her shoulder, telling her that she's too pretty to wear a frown. When he tickles her later and asks her to keep it a secret, Claire doesn't know exactly what's wrong, but something just feels "weird." Too much flattery and too much contact give her that weird, uh-oh feeling. She turns to her friends for help and learns that adults shouldn't ask kids to keep secrets about touch, so Claire tells her mother. By seeking help from others and talking about her feelings, the situation is resolved happily."--